Pengaruh Passive Leg Raising (PLR) terhadap Perubahan Tekanan Darah pada Pasien dengan General Anestesi di RSUD Dr. Soedirman Kebumen - Jihan Sajidah; Jenita Doli Tine Donsu; Harmilah Harmilah (Poltekkes Kemenkes Yogyakarta, 2020)
Induction in patients with general anesthesia can cause blood pressure instability due to vasodilation of arteries and veins. This complication of blood pressure instability must be prevented to restore oxygenation of tissues and organs by giving Passive Leg Raising (PLR). The purposes of this research is to knowing the effect of Passive Leg Raising (PLR) toward the blood pressure change of patients with general anesthesia at Dr. Soedirman Hospital Kebumen. This type of research is quassy experiment with a “pretest-posttest with control group design”. The population was surgical patients with general anesthesia at Dr. Soedirman Kebumen Hospital in January-March 2020. The sampling technique used is random sampling, with inclusion criteria 1. Patients aged 22-55 years, 2. Physical status ASA I-II, 3. Pasien with general anesthesia techniques LMA, TIVA, and Face. The sample consisted of 62 consisting of 31 respondents of the intervention group and 31 respondents of the control group. Data analysis used univariate and bivariate with Paired t-test and Independent t-test. The results was showing that there was a change of blood pressure after given PLR. It was showing by the result of a pretest less than posttest with p value 0.000 and the intervention group experienced a significant increase change over the control group in blood pressure evidenced by the value p value of < 0.05. The conclusion that Passive Leg Raising (PLR) can be influencing blood pressure of patient with general anesthesia